165k views
1 vote
Solve -7(m-1)= -(3m-1)

Please give work

User Svenyonson
by
4.3k points

2 Answers

7 votes

−7 (m − 1)= −(3m − 1)

Use the distributive property to multiply −7 by m−1.

−7m+7=−(3m−1)

To find the opposite of 3m−1, find the opposite of each term.

−7m + 7 = −3m −( − 1 )

The opposite of −1 is 1.

−7m + 7= −3m + 1

Add 3m to both sides.

−7m + 7 + 3m = 1

Combine −7m and 3m to get −4m.

−4m + 7 = 1

Subtract 7 from both sides.

−4m = 1 − 7

Subtract 7 from 1 to get −6.

−4m = −6

Divide both sides by −4.

m = -6/-4

Reduce the fraction -6/-4 to its lowest expression by extracting and canceling −2.

Answer: m=3/4 ✅

User Kahlua
by
5.1k points
1 vote

Answer:

m = 3/2

Explanation:

-7(m-1)= -(3m-1)

-7m + 7 = -3m + 1

-4m = -6

m = 3/2


Check.
-7(m-1)= -(3m-1)

-7(3/2 - 1) = -(3*3/2 - 1)

-7(1/2) = -(4.5 - 1)

-3.5 = -3.5

User Eugene Talagrand
by
5.0k points